Description of electrophoretic and chromatographic hemoglobin profile of Rhinoclemmys punctularia - Bonini-Domingos, C. R. [UNESP]; Silva, M. B. [UNESP]; Romero, R. M. [UNESP]; Zamaro, P. J A [UNESP]; Ondei, L. S. [UNESP]; Zago, C. E S [UNESP]; Moreira, S. B.; Salgado, C. G. (My University, 2007)
Studies of the hemoglobin pattern in Brazilian reptiles are important for determining ecological and phylogenetic relationships, but they are scarce. Peripheral blood samples were obtained from 7 males and 18 females of Rhinoclemmys punctularia. The hematological profile was based on the total hemoglobin and hematocrit values. The hemoglobin profile was obtained using electrophoretic procedures at different pH, isoelectric focusing, globin chain electrophoresis, and HPLC. The hematocrit (31 ± 2%) and total hemoglobin (7.5 ± 0.2 g/dL) values did not indicate gender variations. Alkaline pH electrophoresis of the total blood samples treated with 1% saponin demonstrated the presence of four well-defined hemoglobin fractions, one major component (fraction I), showing cathodic migration and three others faster than fraction I with anodic migration. When the samples were precipitated with chloroform, only two hemoglobin fractions were observed, similar to fractions I and III from the first procedure. Isoelectric focusing and HPLC showed the same pattern. With acid and neutral pH electrophoresis, two fractions with anodic migration were observed. The globin chain identification at alkaline pH showed two fractions, but four fractions were observed at acidic pH, suggesting that different polypeptide chains are involved in the hemoglobin molecule. The chromatographic separation of the total blood sample demonstrated that the major fraction comprised 81.9% and the minor 18.1%. The results obtained demonstrated a similarity between these hemoglobin components and those of some Chelidae reported in the literature for both land and aquatic animals, reflecting the adaptation to environmental conditions. ©FUNPEC-RP.
Keywords: Electrophoretic profile; Hemoglobin polymorphism; Hemoglobins; Rhinoclemmys punctularia; chloroform; hemoglobin; alkalinity; controlled study; electrophoresis; female; hematocrit; hemoglobin determination; high performance liquid chromatography; isoelectric focusing; male; nonhuman; pH; pH measurement; sex difference; turtle; Animals; Chromatography; Ecology; Electrophoresis; Female; Hematocrit; Humans; Male; Models, Genetic; Phylogeny; Polymorphism, Genetic; Reptiles; Turtles; Animalia; Chelidae; Reptilia